Antibacterial Effectiveness Test of Methanil Extract of Brown Algae (Sargassum vulgare) Against Staphylococcus aureus Bacteria - Dieta Andaristi; Irwandi , Irwandi; A.M. Muslihin (Jurnal EduHealth, 2025)
Infectious diseases are one of the main causes of morbidity and mortality globally, especially in developing countries. One of the most common and dangerous pathogenic bacteria is Staphylococcus aureus, that can cause a range of infections by mild skin problems to life-threatening diseases. This study aimed to evaluate the antibacterial activity of methanol extract of brown algae Sargassum vulgare against S. aureus. This laboratory-based experimental research was conducted. Extraction was carried out utilizing the maceration technique with methanol solvent. Phytochemical screening was performed to detect alkaloids, flavonoids, saponins, and steroids. Antibacterial activity was tested utilizing the disk diffusion technique at extract concentrations of 5%, 10%, and 15%, with chloramphenicol as the positive control and aqua pro injection as the negative control. The outcomes performed that the extract contained alkaloids, flavonoids, and saponins, but not steroids. However, no inhibition zone was observed at any extract concentration against S. aureus. In conclusion, although the extract contained bioactive compounds, it did not perform antibacterial effectiveness against S. aureus.